Drop‐on‐Demand Inkjet Printing of Thermally Tunable Liquid Crystal Microlenses. Issue 3 (29th November 2017) - Parry, Ellis; Bolis, Serena; Elston, Steve J.; Castrejón‐Pita, Alfonso A.; Morris, Stephen M.
Abstract : In this letter, the authors demonstrate Drop‐on‐Demand printing of variable focus, polarization‐independent, liquid crystal (LC) microlenses. By carefully selecting the surface treatment applied to a glass substrate, the authors are able to deposit droplets with a well‐defined curvature and contact angle, which result in micron‐sized lenses with focal lengths on the order of 300–900 µm. Observations with an optical polarizing microscope confirm the homeotopic alignment of the LC director in the droplets, which is in accordance with the polarization independent focal length. Results show that microlenses of different focal lengths can be fabricated by depositing successive droplets onto the same location on the substrate, which can then be used to build up programmable and arbitrary arrays of microlenses of various lens sizes and focal lengths. Finally, the authors utilize the thermal dependency of the order parameter of the LC to demonstrate facile tuning of the focal length. This technique has the potential to offer a low‐cost solution to the production of variable focus, arbitrary, microlens arrays. Abstract : Tuneable microlens arrays are fabricated via the drop‐on‐demand inkjet printing of a nematic liquid crystal onto a polymer coated substrate. The programmable and arbitrary microlens arrays produced exhibit excellent polarization independent focussing properties with high numerical apertures.